Application of the First-to-File System in Preventing Passing Off Actions against Registered Mark Holder - Wibowo, Sigit; (郑实), Zheng Shi; Linh, Le Thi Khanh (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2023)
Applying the "First-to-File" principle impacts the first trademark user and the owner who has not yet registered. Another party previously registered the Mark can replace the true trademark owner. It will harm the brand owner who has previously run a business using that brand name. On the other hand, the first-to-file principle means the state should not provide registration for a mark that has similarities with the Mark submitted earlier of similar goods/services, but in this case, the Ministry of Law and Human Rights cannot cancel a registered mark. So passing off actions against registered Mark could occur. This research examines and analyzes the legal protection for registered trademark owners regarding applying the first-to-file principles for those who pass off a registered mark. The research uses a normative juridical research method. The approach is the statutory and case approach, and it uses qualitative analysis methods based on data and substance from various literature such as books, journals, scientific papers, laws, and regulations. This research shows that the form of legal protection for registered trademark owners is related to applying the First-to-File principles to the passing of other parties. It is based on the case analysis of the Supreme Court decision, which stated that the Plaintiff (holder of the Iwan Tirta mark) is the sole legal owner and rights holder of brands that have a dominant element using the word "Iwan Tirta" in all Classes registered, and cancels or declares null and void with all legal consequences the registration of the registered "Pusaka Iwan Tirta & Logo" Mark, as well as punishes the Defendant (PT Pustaka Iwan Tirta) to pay court costs. It means legal action in the form of a lawsuit to the Commercial Court, based on the new Decision, can be used to cancel the registered Mark.